Bias in patient satisfaction surveys: a threat to measuring healthcare quality. Issue 2 (12th April 2018) - Dunsch, Felipe; Evans, David K; Macis, Mario; Wang, Qiao
Abstract : Patient satisfaction surveys are an increasingly common element of efforts to evaluate the quality of healthcare. Many patient satisfaction surveys in low/middle-income countries frame statements positively and invite patients to agree or disagree, so that positive responses may reflect either true satisfaction or bias induced by the positive framing. In an experiment with more than 2200 patients in Nigeria, we distinguish between actual satisfaction and survey biases. Patients randomly assigned to receive negatively framed statements expressed significantly lower levels of satisfaction (87%) than patients receiving the standard positively framed statements (95%—p<0.001). Depending on the question, the effect is as high as a 19 percentage point drop (p<0.001). Thus, high reported patient satisfaction likely overstates the quality of health services. Providers and policymakers wishing to gauge the quality of care will need to avoid framing that induces bias and to complement patient satisfaction measures with more objective measures of quality.